A154 PROTEOMIC IDENTIFICATION OF INFLAMMATORY AND FIBROSTENOTIC BLOOD SERUM BIOMARKERS IN CROHN'S DISEASE. (4th March 2021) - Mainoli, B; Filyk, A K; Lu, C; Dufour, A
Abstract: Background: Crohn's disease (CD) is an incurable relapsing-remitting inflammatory bowel disease (IBD) where patients may experience bowel damage with symptoms such as abdominal pain, chronic diarrhea, extraintestinal manifestations and life-long disability. CD is heterogeneous with three distinct phenotypes including a stricturing phenotype marked by intestinal fibrosis. This fibrotic morphology is generally more unresponsive to drug treatment; delaying a patient's remission, control of the disease and often requiring surgical intervention. Thus, early and accurate identification of fibrostenosis in CD is important to optimize patient treatment and predict response to therapy. Aims: The aim of our study is to distinguish inflammatory and intestinal fibrostenosis in CD patients using serum protein biomarkers. Methods: Blood sera from 17 inflammatory and 17 fibrostenotic CD patients were collected. The phenotypic classification was confirmed by intestinal ultrasound and endoscopy. Samples were subjected to Shotgun Proteomics, an unbiased proteomics approach that allows for relative protein quantification. Proteins from each condition were isotopically labelled with formaldehyde (light +28 Da and heavy +34 Da), pooled and digested with trypsin. Following liquid chromatography and tandem mass spectrometry, peptides were then identified by MaxQuant software with a false discovery rate of 1%. Excel (Microsoft), Prism (Graphpad) and Metascape software were used for data filtering and analysis. Results: Proteomic processing allowed for the identification of novel protein biomarkers in the inflammatory and stricture CD phenotypes. Inflammation was correlated with activation of the complement pathway and fatty acid metabolism; marked by increased levels of immunoglobulin gamma 4 chain (IGHG4), mitochondrial creatinine kinase (CKMT1), apolipoprotein A (LPA) and glutathione peroxidase 3 (GPX3) proteins. Fibrostenosis showed no distinct metabolic pathway, but an elevated expression of SWI/SNF-related matric associated actin (SMARCA5), haptoglobin related protein (HPR), immunoglobulin kappa and immunoglobulin heavy constant proteins. Conclusions: Our data indicate that inflammation and strictures in CD may be driven by distinct signaling pathways. We identified specific protein signatures for the two phenotypes, which may aid in predicting those who are at risk of developing strictures and in the development of phenotype-specific treatment for CD patients. Future validation of these proteins will be performed to assess this unique protein profile. Funding Agencies: McCaig Institute for Bone and Joint Health